Creating A Research Idea: Steps And Challenges - Fernanda Oliveira de Andrade Lopes; Aura Maria Hurtado-Puerto; Heitor Moreno; Felipe Fregni; Denise Pinheiro Falcão; Rivadavio Fernandes Batista de Amorim (Brazilian Society of Geriatrics and Gerontology, 2024)
BACKGROUND: This article is part of a special series designed to help health professionals in the process of developing a research project and writing a manuscript. The research question is the keystone in this process, and represents the first step of every research project. However, its importance is frequently neglected. OBJECTIVE: To highlight important considerations in the development and formulation of a research idea, with the purpose of identifying main guiding elements, in order to prevent errors in one of the most important stages of an experiment. METHODS: The authors performed a non-systematic literature review (PubMed.gov - U.S. National Library of Medicine/National Institute of Health) to retrieve papers that addressed the main steps to build a research question. RESULTS: The construction process includes the conception of the research idea, seeking an appropriate environment and resources, performing a literature review, then crafting and refining the research question, while being aware of potential challenges and pitfalls that may be encountered. The FINER and PICOT criteria can be useful tools in this process. CONCLUSION: It is essential to invest time, energy, and resources in the construction of the research question prior to detailing the study design, thus supporting the further development of the research project on a solid initial foundation.